The Influence of Confucian Economic Thought on China’s Economic Reform - Adrián Cuevas Talens (Iberian Journal of the History of Economic Thought)
This study examines the influence of Confucian economic thought on Chinese economic reforms from the late 20th century to the present. It will analyze how Confucian principles, which emphasize social harmony, respect for authority, and the importance of education and morality, have influenced the formulation and implementation of economic policies in China. Additionally, the reinterpretation of these ideas in the modern context and their impact on the country's economic structure and development will be explored. The article will also compare these approaches with contemporary Western economic ideas, providing an integrated view of the history of economic thought.